Preliminary report: homology modeling of human ryanodine receptor-1 - Waraphan Toniti (2016)
Excitation-contraction (E-C) coupling is the series of events in which an electrical stimulus is converted into a mechanical contraction. Ryanodine receptors (RyRs), the Ca2+ release channels, located at the sarcoplasmic reticulum membrane and played role in E-C coupling. In this study, human RyR1sequence was studied by sequence of P21817. The in silico RyR1 models were generated using homology modeling. RyR1 is the largest known ion channels and composes of 15 important subdomains; cytoplasmic assembly and transmembrane assembly. This study focused on the larger cytoplasmic assembly that is composed of 10 subdomains. The results show that the shapes and the pocket sites of each domain of RyR1 are different. Each domain has its own pocket sites which facilitateinteraction between RyR1 and modulators. Future studies will certainly resolve additional structural differences among species of interest and may apply as model of calcium release channel-modulator interaction.